Carbon nanotube modified fiber composite material as well as preparation method and application thereof
By electrolessly plating nickel-based catalysts on the fiber surface and growing carbon nanotubes, the problems of carbon nanotube agglomeration and low magnetic properties are solved, and efficient catalyst loading and good electromagnetic wave absorption performance are achieved.
Patent Information
- Application Number
- CN202411748083.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
AI Technical Summary
When used directly, carbon nanotubes are prone to agglomeration and difficulty in dispersion due to their high specific surface energy, and their magnetic properties are low.
The nickel-based catalyst is coated on the fiber surface by electroless plating, and carbon nanotubes are grown thereon to form an array structure to adjust the loading and bonding strength of the catalyst.
It effectively improves the load and bonding strength of the catalyst, improves the catalytic environment of carbon nanotubes on the fiber surface, improves the growth density and load of carbon nanotubes, and obtains fiber composite materials with good electromagnetic wave absorption properties.
Smart Images

Figure CN119663629A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite material preparation, and specifically relates to a carbon nanotube modified fiber composite material and a preparation method and application thereof. Background Art
[0002] Carbon nanotubes are cylindrical shells with a diameter of nanometers, which are formed by curling one or more layers of graphite sheets at a certain spiral angle. According to the number of graphite sheets, carbon nanotubes can be divided into single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes. Carbon nanotubes inherit a series of excellent properties of graphite, such as heat resistance, corrosion resistance, good heat transfer and electrical conductivity, high high-temperature strength, etc. Carbon nanotubes are a kind of star material with a tubular structure composed entirely of a single light element carbon in the form of modified sp2 hybrid covalent bonds. Due to its unique one-dimensional structure and nanometer-scale size, it has many excellent properties. It not only has excellent mechanical, optical, and magnetic properties, but also has flexible and variable electrical properties and excellent thermal conductivity. It is a frontier research object in physics, chemistry, electronics, materials science and other disciplines.
[0003] In the field of absorbing materials, carbon nanotubes can effectively absorb and scatter electromagnetic waves and reduce reflectivity due to their extremely high specific surface area and aspect ratio. Secondly, the lightweight and easy processing characteristics of carbon nanotubes make them suitable for various applications, whether as fillers or coatings. However, carbon nanotubes have a high specific surface energy, and when used directly, they will inevitably agglomerate and be difficult to disperse. Summary of the invention
[0004] In view of this, the main purpose of the present invention is to provide a carbon nanotube modified fiber composite material and its preparation method and application. The problem to be solved is to firmly and completely coat the nickel-based catalyst on the fiber surface by chemical plating, which can effectively increase the catalyst loading and bonding strength; in addition, the loading amount of the metal catalyst on the fiber surface can be adjusted by chemical plating, and the nickel-based catalyst can make up for the disadvantage of the low magnetic properties of carbon nanotubes.
[0005] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. A method for preparing a carbon nanotube modified fiber composite material proposed by the present invention comprises the following steps:
[0006] Step 1, cutting the fiber material and performing heat treatment;
[0007] Step 2, immersing the fiber material obtained in step 1 in a chemical plating solution for heat preservation, so that the surface of the fiber is coated with a nickel-based catalyst;
[0008] Step three, growing carbon nanotubes on the fiber with the surface coated with nickel-based catalyst obtained in step two in the presence of reaction gas to obtain the carbon nanotube-modified fiber composite material.
[0009] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0010] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step 1, the fiber material is selected from at least one of glass fiber, carbon fiber, silicon carbide fiber and basalt fiber.
[0011] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step 1, the temperature of the heat treatment is 600-800° C.; and the time of the heat treatment is 20-40 min.
[0012] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step 2, the chemical plating solution is a mixed solution of hexahydrate and nickel sulfate, sodium hypophosphite, sodium citrate, ammonium chloride and ammonia water.
[0013] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step 2, in the chemical plating solution, the mass ratio of the nickel sulfate hexahydrate, sodium hypophosphite, sodium citrate, ammonium chloride and water is 2-5:0.5-2:1-3:3-6:100.
[0014] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step 2, the pH value of the chemical plating solution is 8-10.
[0015] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step 2, the insulation temperature is 60 to 90° C.; and the insulation time is 5 min to 60 min.
[0016] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the temperature at which the carbon nanotubes grow is 500-850°C.
[0017] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the reaction gas includes a protective gas, a carbon source gas and a reducing gas.
[0018] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the protective gas is selected from at least one of argon, nitrogen and helium.
[0019] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the flow rate of the protective gas is 500-2000 sccm.
[0020] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the reducing gas is hydrogen.
[0021] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the flow rate of the reducing gas is 50 to 1000 sccm.
[0022] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the carbon source gas is selected from at least one of methane, acetylene and ethylene.
[0023] Preferably, in the aforementioned method for preparing the carbon nanotube-modified fiber composite material, in step three, the flow rate of the carbon source gas is 50-500 sccm.
[0024] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a carbon nanotube modified fiber composite material, which comprises fibers, carbon nanotubes and a Ni-based catalyst, wherein the surface of the fibers is coated with a nickel-based catalyst, carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotubes is 10 to 30 nm.
[0025] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0026] Preferably, the aforementioned carbon nanotube-modified fiber composite material has a tensile strength of 793 to 1786 MPa, a specific gravity of carbon nanotubes of 47.23 wt% to 81.02 wt%, and an optimal wave absorbing performance of -52.26 to -19.62 dB.
[0027] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a fiber absorbing material, which includes a carbon nanotube-modified fiber composite material, which includes a fiber, a carbon nanotube and a Ni-based catalyst, the surface of the fiber is coated with a nickel-based catalyst, and carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotubes is 10 to 30 nm.
[0028] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0029] Preferably, the aforementioned fiber absorbing material is a resin-based composite material reinforcement, a absorbing coating, an absorbing filler or an absorbing material substrate.
[0030] By means of the above technical solution, the present invention provides a carbon nanotube modified fiber composite material and a preparation method and application thereof, which have at least the following advantages:
[0031] The present invention provides a method for growing carbon nanotubes based on chemical nickel plating on the fiber surface, which can solve the problem of weak catalyst bonding in the existing substrate method for preparing carbon nanotubes.
[0032] The present invention can adjust the loading amount and coating thickness of the catalyst on the fiber surface by adjusting the chemical plating process, thereby improving the catalytic environment of the carbon nanotubes on the fiber surface;
[0033] The present invention can effectively increase the growth density and loading amount of carbon nanotubes on the fiber surface;
[0034] The present invention can obtain a fiber composite material with good electromagnetic wave absorption performance by nickel plating on the fiber surface and growing carbon nanotubes;
[0035] The tensile strength of the carbon nanotube modified fiber composite material of the invention is 793-1786 MPa, the specific gravity of the carbon nanotube is 47.23 wt%-81.02 wt%, and the best wave absorbing performance is -52.26--19.62 dB.
[0036] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM image of the carbon nanotube-modified fiber composite material of Example 1 of the present invention;
[0038] Figure 2 This is a SEM image of the surface of the fiber coated with nickel-based catalyst after chemical nickel plating in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a carbon nanotube modified fiber composite material and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0040] The following materials or reagents, unless otherwise specified, were commercially available.
[0041] Some embodiments of the present invention provide a method for preparing a carbon nanotube-modified fiber composite material, comprising the following steps:
[0042] Step 1: Cut the fiber material into pieces of 5-20 cm and perform heat treatment to remove organic matter that may exist on the fiber surface; the cutting length needs to match the effective temperature zone (about 25 cm) of the high-temperature tube furnace used;
[0043] Step 2, preparing a chemical plating solution, immersing the fiber in the chemical plating solution, and keeping the temperature, so that the surface of the fiber is coated with a nickel-based catalyst;
[0044] Step 3: Feed the catalyst-coated fiber obtained in step 2 into a high-temperature tube furnace to grow carbon nanotubes in the presence of a reaction gas to obtain the carbon nanotube / fiber composite material. Growing carbon nanotubes directly on the surface of fibers with excellent mechanical properties can solve the problem of carbon nanotube agglomeration.
[0045] In the above technical scheme, the present invention attaches a nickel-based catalyst to the surface of the fiber by chemical plating, and then directly grows carbon nanotubes on the fiber surface by chemical vapor deposition, and finally obtains a carbon nanotube-modified fiber composite material with wave absorbing ability. The problem of low adhesion of the catalyst to the fiber surface in the substrate method can be effectively improved by the chemical plating method. In addition, since the fiber itself has the characteristics of a high aspect ratio, the time and cost requirements for chemical plating are relatively low, and the complete coating of the fiber with a nickel-based catalyst can be completed in a relatively short time. A fiber composite material with good electromagnetic wave absorbing performance can be obtained by nickel plating the fiber surface and growing carbon nanotubes.
[0046] In some optional embodiments, in step 1, considering the electrical properties and wave absorbing properties of the fiber, the fiber can be selected from at least one of glass fiber, carbon fiber, silicon carbide fiber and basalt fiber.
[0047] In some optional embodiments, in step 1, considering that the slurry on the fiber surface is organic, the heat treatment temperature can be set to 400-800°C, preferably 550-750°C, in order to accelerate the decomposition of the slurry and reduce the damage to the fiber strength; if the heat treatment temperature is lower than 400°C, the slurry on the fiber surface cannot be eliminated; if the heat treatment temperature is higher than 800°C, the strength of the fiber matrix may be damaged; the heat treatment time is 20-40 minutes, preferably 25-35 minutes, in order to remove the organic matter on the surface while minimizing the damage to the fiber. If the heat treatment time is less than 20 minutes, the organic matter on the fiber surface may not be removed; if the heat treatment time is greater than 40 minutes, the fiber structure will be damaged if the time is too long.
[0048] In some optional embodiments, in step 2, the chemical plating solution can be a mixed solution of hexahydrate and nickel sulfate, sodium hypophosphite, sodium citrate, ammonium chloride and ammonia water. Specifically, in the chemical plating solution, the mass ratio of the nickel sulfate hexahydrate, sodium hypophosphite, sodium citrate, ammonium chloride and water is 2-5:0.5-2:1-3:3-6:100. The ammonia water is used to adjust the pH value of the chemical plating solution. The functions of these components are solvent, nickel source, reducing agent, stabilizer and complexing agent respectively. The ratio of nickel sulfate hexahydrate and ammonium chloride in this ratio is critical. Mismatch between the two may lead to incomplete dissolution or the generation of new precipitation. Sodium hypophosphite is to reduce Ni to metal deposition on the fiber surface. Too low reduction is insufficient, and too high may cause side reactions. Sodium citrate is to form a buffer system to stabilize the pH value of the solution for a long time.
[0049] In some optional embodiments, in step 2, chemical nickel plating requires an alkaline environment, and the pH range of the chemical plating solution is set to 8-10, preferably 8.5-9.5, which is preferably to obtain a better Ni-based coating. If the pH value is less than 8, the pH value is too low and the reaction is insufficient; if the pH value is greater than 10, the pH value is too high and may cause nickel hydroxide precipitation.
[0050] In some optional embodiments, in step 2, the temperature of the insulation is 60-90°C, preferably 70-80°C. The purpose of heating is to increase the reaction rate and improve the quality of precipitation. If the temperature is lower than 60°C, the too low temperature cannot play a good role in accelerating the reaction; and the chemical plating solution is corrosive. If the temperature is higher than 90°C, the excessively high temperature will cause serious corrosion to the fiber surface.
[0051] In some optional embodiments, in step 2, the insulation time is 5min to 60min, preferably 15min to 45min, so that the Ni coverage is more sufficient and the fiber strength is less damaged. The purpose of adjusting the time is to adjust the thickness and quality of the Ni layer on the fiber surface. If the time is less than 5min, the effect of chemical plating is not good when the time is too short; if the time is more than 60min, the fiber structure will be seriously damaged if the time is too long.
[0052] In some optional embodiments, in step three, the temperature of the carbon nanotube growth is 500-850°C, preferably 600-750°C, which is the CVD range of Ni-based catalysts, and the grown carbon nanotubes have high density and good uniformity. The decomposition of the carbon source gas requires a high temperature environment. If the temperature is lower than 500°C, the decomposition is incomplete due to the low temperature; if the temperature is higher than 850°C, the carbon source gas decomposes too quickly due to the high temperature, and the fiber is damaged.
[0053] In some optional embodiments, in step 3, the reaction gas includes a protective gas, a carbon source gas and a reducing gas. The protective gas is a carrier gas that balances the atmosphere; the carbon source gas decomposes at high temperature and is the raw material of carbon nanotubes; the reducing gas reduces the catalyst to a suitable valence state, improves the catalytic activity, and at the same time inhibits the decomposition rate of the carbon source gas to a certain extent, thereby improving the product quality.
[0054] In some optional embodiments, in step three, the protective gas can be selected from at least one of argon, nitrogen, and helium, which serves as a carrier gas and does not participate in the reaction.
[0055] In some optional embodiments, in step 3, the flow rate of the protective gas can be set to 500-2000 sccm, preferably 1200-1600 sccm. The functions of the protective gas are to dilute other reaction gases to improve safety and to balance the gas ratio to construct a suitable atmosphere. If the flow rate is lower than 500 sccm, the flow rate will not work; if the flow rate is higher than 2000 sccm, the flow rate will be too high, which will lead to unstable atmosphere and poor product quality.
[0056] In some optional embodiments, in step 3, the reducing gas may be hydrogen gas, considering the reduction effect and safety, in order to reduce the cracking rate of the carbon source gas and improve the uniformity of the growth of the carbon nanotubes. If the reducing gas is not used, the growth of the carbon nanotubes is obviously more disorderly and unevenly distributed.
[0057] In some optional embodiments, in step 3, the carbon source gas, the protective gas and the reducing gas need to be balanced with each other, and the flow rate of the reducing gas can be set to 50-1000 sccm, preferably 400-600 sccm. If the flow rate is less than 50 sccm, the too low flow rate will result in an insignificant reduction effect; if the flow rate is greater than 1000 sccm, the too high flow rate will destroy the balance of the gas components.
[0058] In some optional embodiments, in step three, the carbon source gas can be selected from at least one of methane, acetylene and ethylene.
[0059] In some optional embodiments, in step 3, the carbon source gas provides a carbon source for growing carbon nanotubes. The flow rate of the carbon source gas can be set to 50-500 sccm, preferably 200-400 sccm, so that the structural density of the carbon nanotubes grown later is relatively uniform. If the flow rate is less than 50 sccm, the too low flow rate limits the growth of carbon nanotubes; if the flow rate is greater than 500 sccm, the too high flow rate will cause the carbon nanotubes to grow uncontrolled and produce side reactions.
[0060] Some embodiments of the present invention also provide a carbon nanotube-modified fiber composite material, which includes fibers, carbon nanotubes and a Ni-based catalyst, the surface of the fibers is coated with a nickel-based catalyst, carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotubes is 10 to 30 nm; the tensile strength of the carbon nanotube-modified fiber composite material is 793 to 1786 MPa, the specific gravity of the carbon nanotubes is 47.23wt% to 81.02wt%, and the optimal wave absorbing efficiency is -52.26 to -19.62 dB; the carbon nanotube-modified fiber composite material is prepared by the above method.
[0061] Some embodiments of the present invention also provide a fiber absorbing material, which includes a carbon nanotube-modified fiber composite material, wherein the carbon nano-modified fiber composite material includes fibers, carbon nanotubes and a Ni-based catalyst, the surface of the fiber is coated with a nickel-based catalyst, carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotubes is 10 to 30 nm.
[0062] Specifically, the fiber absorbing material can be a resin-based composite material reinforcement, an absorbing coating, an absorbing filler or an absorbing material substrate.
[0063] The specific implementation methods of the present invention are further described in detail below in conjunction with the embodiments, but it should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0064] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0065] Example 1
[0066] This embodiment provides a method for preparing a carbon nanotube-modified fiber composite material, comprising the following steps:
[0067] (1) cutting the glass fiber into a length of 20 cm, and heat treating it at 750° C. for 30 min in an argon atmosphere with a purity of 99.99%, to remove the sizing agent and other organic matter on the fiber surface, thereby obtaining a bare glass fiber;
[0068] (2) 30 g of nickel sulfate hexahydrate, 12 g of sodium hypophosphite, 25 g of sodium citrate, and 50 g of ammonium chloride were added to 1 L of deionized water, and the pH value was adjusted to 8 with ammonia water to obtain a chemical plating solution; the temperature of the chemical plating solution was maintained at 70° C., and the treated glass fiber bare wire was immersed in the chemical plating solution for 30 minutes to obtain a glass fiber coated with a nickel-based catalyst. Figure 2 ;from Figure 2 It can be seen that the Ni catalyst completely covers the surface of the fiber, and the brighter spots in the figure are caused by a few Ni catalysts with relatively large particles showing high conductivity;
[0069] (3) The glass fiber coated with the catalyst is sent into a high-temperature tube furnace, and argon gas (purity of 99.99%) with a flow rate of 1500sccm is introduced, and the furnace is heated to 700°C; at this time, 500sccm of hydrogen is introduced, and the temperature is kept for 10 minutes; methane is then introduced without closing the hydrogen gas line, with a flow rate of 300sccm, and the temperature is kept for 5 minutes; then the hydrogen and methane are closed, and the quartz tube is cooled to room temperature in an argon atmosphere (purity of 99.99%) to obtain the carbon nanotube-modified fiber composite material, including fibers, carbon nanotubes and Ni-based catalysts, wherein the surface of the fibers is coated with a nickel-based catalyst, and carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotubes is about 20nm, see Figure 1 .from Figure 1 It can be seen that the carbon nanotubes grow outward with the Ni-based catalyst coated on the fiber surface as the substrate to form an array structure.
[0070] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of resin-based composite material reinforcement.
[0071] Example 2
[0072] This embodiment provides a method for preparing a carbon nanotube-modified fiber composite material, comprising the following steps:
[0073] (1) Cut the glass fiber into a length of 20 cm, and heat-treat it at 750° C. for 30 min in an argon atmosphere with a purity of 99.99% to remove the sizing agent and other organic matter on the fiber surface to obtain a bare glass fiber.
[0074] (2) 30 g of nickel sulfate hexahydrate, 12 g of sodium hypophosphite, 25 g of sodium citrate, and 50 g of ammonium chloride were sequentially added into 1 L of deionized water, and the pH value was adjusted to 8 with aqueous ammonia to obtain a chemical plating solution;
[0075] The temperature of the chemical plating solution was maintained at 90° C., and the treated bare glass fiber was immersed in the chemical plating solution for 30 minutes to obtain glass fiber coated with a nickel-based catalyst.
[0076] (3) The glass fiber coated with the catalyst is sent into a high-temperature tube furnace, an argon flow rate of 1500sccm is introduced, and it is heated to 700°C; at this time, 500sccm of hydrogen is introduced and the temperature is kept for 10 minutes; methane is then introduced without closing the hydrogen gas line, with a flow rate of 300sccm, and the temperature is kept for 5 minutes; then the hydrogen and methane are closed, and the quartz tube is cooled to room temperature in an argon atmosphere (purity of 99.99%), to obtain the carbon nanotube-modified fiber composite material including fiber, carbon nanotube and Ni-based catalyst, the surface of the fiber is coated with a nickel-based catalyst, carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotube is about 20nm.
[0077] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of radar absorbing coatings.
[0078] Example 3
[0079] This embodiment provides a method for preparing a carbon nanotube-modified fiber composite material, comprising the following steps:
[0080] (1) Cut the glass fiber into a length of 20 cm, and heat-treat it at 750° C. for 30 min in an argon atmosphere with a purity of 99.99% to remove the sizing agent and other organic matter on the fiber surface to obtain a bare glass fiber.
[0081] (2) 30 g of nickel sulfate hexahydrate, 12 g of sodium hypophosphite, 25 g of sodium citrate, and 50 g of ammonium chloride were sequentially added into 1 L of deionized water, and the pH value was adjusted to 8 with aqueous ammonia to obtain a chemical plating solution;
[0082] The temperature of the chemical plating solution was maintained at 70° C., and the treated bare glass fiber was immersed in the chemical plating solution for 15 minutes to obtain glass fiber coated with a nickel-based catalyst.
[0083] (3) The glass fiber coated with the catalyst is sent into a high-temperature tube furnace, an argon flow rate of 1500sccm is introduced, and it is heated to 700°C; at this time, 500sccm of hydrogen is introduced and the temperature is kept for 10 minutes; methane is then introduced without closing the hydrogen gas line, with a flow rate of 300sccm, and the temperature is kept for 5 minutes; then the hydrogen and methane are closed, and the quartz tube is cooled to room temperature in an argon atmosphere (purity of 99.99%), to obtain the carbon nanotube-modified fiber composite material including fiber, carbon nanotube and Ni-based catalyst, the surface of the fiber is coated with a nickel-based catalyst, carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotube is about 20nm.
[0084] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of resin-based composite material reinforcement.
[0085] Example 4
[0086] This embodiment provides a method for preparing a carbon nanotube-modified fiber composite material, comprising the following steps:
[0087] (1) The carbon fiber was cut into a length of 20 cm and heat treated at 750° C. for 30 min in an argon atmosphere with a purity of 99.99% to remove the sizing agent and other organic matter on the fiber surface to obtain bare glass fiber.
[0088] (2) 30 g of nickel sulfate hexahydrate, 12 g of sodium hypophosphite, 25 g of sodium citrate, and 50 g of ammonium chloride were sequentially added into 1 L of deionized water, and the pH value was adjusted to 8 with aqueous ammonia to obtain a chemical plating solution;
[0089] The temperature of the chemical plating solution was maintained at 70° C., and the treated bare glass fiber was immersed in the chemical plating solution for 30 minutes to obtain glass fiber coated with a nickel-based catalyst.
[0090] (3) The glass fiber coated with the catalyst is sent into a high-temperature tube furnace, an argon flow rate of 1500sccm is introduced, and it is heated to 600°C; at this time, 500sccm of hydrogen is introduced and the temperature is kept for 10 minutes; methane is then introduced without closing the hydrogen gas line, with a flow rate of 300sccm, and the temperature is kept for another 10 minutes; then the hydrogen and methane are turned off, and the quartz tube is allowed to cool to room temperature in an argon atmosphere (purity of 99.99%), to obtain the carbon nanotube-modified fiber composite material including fiber, carbon nanotube and Ni-based catalyst, the surface of the fiber is coated with a nickel-based catalyst, carbon nanotubes are grown on the Ni-based catalyst to form an array structure, and the diameter of the carbon nanotube is about 20nm.
[0091] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of wave-absorbing fillers.
[0092] Example 5
[0093] The difference between this embodiment and embodiment 1 is that the heating temperature in step (3) of this embodiment is 600° C., and the remaining steps and parameters are the same as those in embodiment 1.
[0094] The carbon nanotube-modified fiber composite material prepared in this embodiment includes fibers, carbon nanotubes and Ni-based catalysts. The surface of the fibers is coated with nickel-based catalysts. Carbon nanotubes grow on the Ni-based catalysts to form an array structure. The diameter of the carbon nanotubes is about 20 nm.
[0095] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of wave-absorbing fillers.
[0096] Example 6
[0097] The difference between this embodiment and embodiment 1 is that the continued insulation time in step (3) of this embodiment is 15 minutes, and the remaining steps and parameters are the same as those in embodiment 1.
[0098] The carbon nanotube-modified fiber composite material prepared in this embodiment includes fibers, carbon nanotubes and Ni-based catalysts. The surface of the fibers is coated with nickel-based catalysts. Carbon nanotubes grow on the Ni-based catalysts to form an array structure. The diameter of the carbon nanotubes is about 20 nm.
[0099] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of resin-based composite material reinforcement.
[0100] Example 7
[0101] The difference between this embodiment and embodiment 1 is that the flow rate of methane in step (3) of this embodiment is 100 sccm, and the remaining steps and parameters are the same as those in embodiment 1.
[0102] The carbon nanotube-modified fiber composite material prepared in this embodiment includes fibers, carbon nanotubes and Ni-based catalysts. The surface of the fibers is coated with nickel-based catalysts. Carbon nanotubes grow on the Ni-based catalysts to form an array structure. The diameter of the carbon nanotubes is about 20 nm.
[0103] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of radar absorbing coatings.
[0104] Example 8
[0105] The difference between this embodiment and embodiment 1 is that the hydrogen flow rate in step (3) of this embodiment is 200 sccm, and the remaining steps and parameters are the same as those in embodiment 1.
[0106] The carbon nanotube-modified fiber composite material prepared in this embodiment includes fibers, carbon nanotubes and Ni-based catalysts. The surface of the fibers is coated with nickel-based catalysts. Carbon nanotubes grow on the Ni-based catalysts to form an array structure. The diameter of the carbon nanotubes is about 20 nm.
[0107] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of wave-absorbing fillers.
[0108] Example 9
[0109] The difference between this embodiment and embodiment 1 is that the amount of deionized water in step (2) of this embodiment is 1500 mL, and the remaining steps and parameters are the same as those in embodiment 1.
[0110] The carbon nanotube-modified fiber composite material prepared in this embodiment includes fibers, carbon nanotubes and Ni-based catalysts. The surface of the fibers is coated with nickel-based catalysts. Carbon nanotubes grow on the Ni-based catalysts to form an array structure. The diameter of the carbon nanotubes is about 20 nm.
[0111] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of wave-absorbing fillers.
[0112] Example 10
[0113] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the nickel sulfate hexahydrate is 20 g, the ammonium chloride is 40 g, and the remaining steps and parameters are the same as those in embodiment 1.
[0114] The carbon nanotube-modified fiber composite material prepared in this embodiment includes fibers, carbon nanotubes and Ni-based catalysts. The surface of the fibers is coated with nickel-based catalysts. Carbon nanotubes grow on the Ni-based catalysts to form an array structure. The diameter of the carbon nanotubes is about 20 nm.
[0115] The carbon nanotube-modified fiber composite material prepared in this embodiment can be used in the preparation of radar absorbing coatings.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is that the temperature of the chemical plating in step (2) of this comparative example is 40° C., and the remaining steps and parameters are the same as Example 1.
[0118] Comparative Example 2
[0119] The difference between this comparative example and Example 1 is that in step (2) of this comparative example, the time for immersing the glass fiber in the chemical plating solution is 120 minutes, and the remaining steps and parameters are the same as those in Example 1.
[0120] Comparative Example 3
[0121] The main difference between this comparative example and Example 1 is that in step (3) of this comparative example, hydrogen is not introduced during the 10 min insulation, and the remaining steps and parameters are the same as those of Example 1.
[0122] Comparative Example 4
[0123] The main difference between this comparative example and Example 1 is that the heating temperature in step (3) of this comparative example is 450° C., and the remaining steps and parameters are the same as Example 1.
[0124] The carbon nanotube modified fiber composite materials of Examples 1-10 and the fiber composite materials of Comparative Examples 1-4 were respectively tested for tensile strength, carbon nanotube specific gravity and wave absorption performance. The carbon nanotube modified fiber composite materials of Examples 1-10 and the fiber composite materials of Comparative Examples 1-4 were respectively uniformly mixed with 10% paraffin wax by mass fraction to form test materials, and then the test materials were made into annular specimens with an inner diameter of 3.04mm, an outer diameter of 7mm and a thickness of 2mm by a stainless steel mold, and then the wave absorption performance of the annular specimens was tested using a vector network analyzer. The carbon nanotube modified fiber composite materials of Examples 1-10 and the fiber composite materials of Comparative Examples 1-4 were respectively tested for their tensile strength by a fiber extensometer. The carbon nanotube modified fiber composite materials of Examples 1-10 and the fiber composite materials of Comparative Examples 1-4 were respectively tested for their carbon nanotube specific gravity by thermogravimetric analysis.
[0125] Table 1 Properties of the carbon nanotube modified fiber composite materials of Examples 1-10 and the fiber composite materials of Comparative Examples 1-4
[0126] <![CDATA[Tensile strength σ b (MPa)]]> Carbon nanotube specific gravity (wt%) Best wave absorption performance (dB) Example 1 1092 67.33 -41.52 Example 2 793 74.21 -52.26 Example 3 1419 61.71 -26.83 Example 4 1786 79.34 -34.62 Example 5 1761 62.13 -31.52 Example 6 837 81.02 -24.29 Example 7 1254 47.23 -21.44 Example 8 944 76.87 -19.62 Example 9 1422 55.74 -38.53 Example 10 1193 61.25 -38.17 Comparative Example 1 1983 27.86 -9.57 Comparative Example 2 512 65.13 -16.73 Comparative Example 3 931 68.11 -11.21 Comparative Example 4 1912 17.85 -9.06
[0127] From the data in Table 1, it can be seen that the tensile strength of the carbon nanotube-modified fiber composite materials of Examples 1-10 of the present invention is 793-1786 MPa, the specific gravity of the carbon nanotubes is 47.23 wt%-81.02 wt%, and the best absorbing performance is -52.26--19.62 dB.
[0128] The temperature and time of chemical plating have a significant effect on the strength of glass fiber. Too high temperature and too long time will cause the strength of glass fiber to drop seriously, and will damage the wave absorption performance of the prepared carbon nanotube modified fiber composite material. The change of the components of chemical plating solution within a certain range will reduce the wave absorption performance of the prepared carbon nanotube modified fiber composite material, but reasonable changes can improve the mechanical properties to a certain extent. The temperature of chemical vapor deposition will affect the catalytic activity of the catalyst. If the temperature is too low, the final carbon nanotube output will be scarce, but too high temperature will destroy the strength of glass fiber. The components of the gas have a significant effect on the wave absorption performance of the finally prepared carbon nanotube modified fiber composite material. The flow rate of carbon source gas directly affects the raw material supply of carbon nanotubes. Too low flow rate will reduce the output of carbon nanotubes. The presence of reducing gas is crucial to obtain carbon nanotubes with good performance. It can be seen from Comparative Example 3 that in the absence of reducing gas, the wave absorption performance of the prepared carbon nanotube modified fiber composite material is significantly reduced when the carbon nanotube loading amount does not change much.
[0129] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0130] The numerical range described in the present invention includes all the numerical values within the range, and includes the range value formed by any two numerical values within the range. Different numerical values of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.
[0131] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0132] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon nanotube-modified fiber composite material, characterized in that: The following steps are involved: Step 1, cutting the fiber material and performing heat treatment; Step 2, immersing the fiber material obtained in step 1 in a chemical plating solution for heat preservation, so that the surface of the fiber is coated with a nickel-based catalyst; Step three, growing carbon nanotubes on the fiber with the surface coated with nickel-based catalyst obtained in step two in the presence of reaction gas to obtain the carbon nanotube-modified fiber composite material.
2. The method for preparing the carbon nanotube-modified fiber composite material according to claim 1, characterized in that: In step 1, the fiber material is selected from at least one of glass fiber, carbon fiber, silicon carbide fiber and basalt fiber; the heat treatment temperature is 600-800° C.; and the heat treatment time is 20-40 min.
3. The method for preparing the carbon nanotube-modified fiber composite material according to claim 1, characterized in that: In step 2, the chemical plating solution is a mixed solution of hexahydrate and nickel sulfate, sodium hypophosphite, sodium citrate, ammonium chloride and ammonia water; in the chemical plating solution, the mass ratio of the nickel sulfate hexahydrate, sodium hypophosphite, sodium citrate, ammonium chloride and water is 2-5:0.5-2:1-3:3-6:100; the pH value of the chemical plating solution is 8-10.
4. The method for preparing the carbon nanotube-modified fiber composite material according to claim 1, characterized in that: In step 2, the insulation temperature is 60-90° C. and the insulation time is 5 min-60 min.
5. The method for preparing the carbon nanotube-modified fiber composite material according to claim 1, characterized in that: In step three, the temperature for growing the carbon nanotubes is 500-850° C.; the reaction gas includes a protective gas, a carbon source gas and a reducing gas.
6. The method for preparing the carbon nanotube-modified fiber composite material according to claim 5, characterized in that: In step three, the protective gas is selected from at least one of argon, nitrogen and helium; the flow rate of the protective gas is 500-2000sccm; the reducing gas is hydrogen; the flow rate of the reducing gas is 50-1000sccm; the carbon source gas is selected from at least one of methane, acetylene and ethylene; the flow rate of the carbon source gas is 50-500sccm.
7. A carbon nanotube modified fiber composite material, characterized in that: The carbon nano-modified fiber composite material comprises fibers, carbon nanotubes and Ni-based catalysts. The surface of the fibers is coated with nickel-based catalysts. Carbon nanotubes grow on the Ni-based catalysts to form an array structure. The diameter of the carbon nanotubes is 10 to 30 nm.
8. The carbon nanotube-modified fiber composite material according to claim 7, characterized in that: The tensile strength of the carbon nanotube modified fiber composite material is 793-1786 MPa, the specific gravity of the carbon nanotube is 47.23wt%-81.02wt%, and the best wave absorbing performance is -52.26--19.62dB.
9. A fiber absorbing material, characterized in that: The fiber absorbing material includes a carbon nanotube modified fiber composite material, which includes fibers, carbon nanotubes and a Ni-based catalyst. The surface of the fiber is coated with a nickel-based catalyst, and carbon nanotubes grow on the Ni-based catalyst to form an array structure. The diameter of the carbon nanotubes is 10 to 30 nm.
10. The fiber absorbing material according to claim 9, characterized in that: The fiber absorbing material is a resin-based composite material reinforcement, a absorbing coating, a absorbing filler or a absorbing material substrate.
Citation Information
Patent Citations
Method for preparing short carbon fiber reinforced magnesium-base composite material with good damping characteristic
CN101705456A
Chemical nickel plating method on carbon fiber surface
CN103981513A
Preparation method of high-performance nickel-plated carbon fibers
CN106801335A
Carbon fiber electromagnetic shielding material and preparation method thereof
CN112724687A
Boron nitride modified silicon carbide fiber growth carbon nanotube ceramic matrix composite material and preparation method thereof
CN116462524A
Cited By
Composite sound absorption material based on carbon nanotube modified glass fibers and preparation method and application thereof
CN121405376A